Analysis Of Metacognition Ability in Mathematic Problem Solving on Student's Learning Creativity - Adinda Permata; Hamdan Sugilar (Gunung Djati Conference Series, 2022)
The purpose of this study was to describe the metacognitive ability in solving mathematical problems on students' learning creativity in solving problems that exist in the description questions with students' creative learning abilities. The type of research used is a descriptive qualitative approach with the research subject used is the results of 18 students of class XII RPL who have been determined by their mathematics teacher. This study focuses on the metacognitive abilities of the students who are expected to have a level with five stages that have been tested, namely very high, high, medium, low, and very low. By using the instrument used in this metacognitive ability research, namely a metacognitive ability test about arithmetic sequences and series that pays attention to students' learning creativity and a questionnaire about students' metacognitive abilities by looking at their mathematical problem solving abilities. The data analysis technique used is drawing conclusions and presenting data from random sampling used from 18 students. The results of the data analysis have aspects that are fulfilled from the five stages tested and aspects of students' mathematical problem solving on students' learning creativity meet their metacognitive abilities